Xanthogranulomatous Cholecystitis and Gallbladder Cancer: Two Diseases with Difficult Differential Diagnoses - Akkurt, Gökhan; Birben, Birkan; Çoban, Serdar; Akgül, Özgür; Kulaçoğlu, Sezer; Doğanay, Mutlu (Turkish Journal of Gastroenterology, 2021)
Background: Xanthogranulomatous cholecystitis (XGC) etiology has not yet been precisely determined; it is often confused with gallbladder cancer (GBC) in the differential diagnosis. Methods:: This study retrospectively evaluated patients who underwent surgery with the pre-diagnosis of cholelithiasis, cholecystitis, or gallbladder carcinoma at a tertiary center, and were confirmed to have XGC or GBC according to the histological examinations. Results: In the GBC group, there was a higher number of female patients, patients with magnetic resonance imaging (MRI) and computed tomography (CT) imaging, those that directly underwent open surgery, and those requiring catheters and developed complications; while in the XGC group, there was a higher number of patients with ultrasonography (USG) imaging and those requiring conversion from laparoscopic to open surgery (P < .05). The rate of patients with a preoperative diagnosis of cholelithiasis was higher in the XGC group than in the GBC group, and cases with intrahepatic bile duct (IHBD) dilatation were higher in the GBC group than in the XGC group, and the GBC group also had a higher rate of cases with a malignant diagnosis in the preoperative examination compared to the XGC group (P < .05). Conclusion: When a suspicious malignant mass is detected in the localization of the gallbladder, XGC must be considered in the differential diagnosis. Although it is not a malignant pathology, early diagnosis and treatment are particularly important due to the associated complications and the possibility of coexistence with GBC.